2016
DOI: 10.1039/c6mb00373g
|View full text |Cite
|
Sign up to set email alerts
|

More than just recruitment: the X-domain influences catalysis of the first phenolic coupling reaction in A47934 biosynthesis by Cytochrome P450 StaH

Abstract: Glycopeptide antibiotic biosynthesis involves a complex cascade of reactions centred on a non-ribosomal peptide synthetase and modifiying proteins acting in trans, such as Cytochrome P450 enzymes. These P450s are responsible for cyclisation of the peptide via cross-linking aromatic amino acid side chains, which are a hallmark of the glycopeptide antibiotics. Here, we analysed the first cyclisation reaction in the biosynthesis of the glycopeptide antibiotic A47934. Our results demonstrate that the P450 StaH is … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
46
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

6
2

Authors

Journals

citations
Cited by 24 publications
(47 citation statements)
references
References 50 publications
1
46
0
Order By: Relevance
“…This corresponds to the absorption spectra characteristic for P450s in the low-spin state, indicating the heme moiety of StaF to be present in its water-bound ferric form. Equivalent spectra were observed for related P450s such as StaH, OxyA tei , OxyB tei and OxyE tei , which are also involved in GPA cyclisation reactions [12,14,19,22]. Reduction of StaF by addition of sodium dithionite led to conversion of ferric to ferrous heme, which was accompanied by shift of the Soret maximum to λ = 422 nm and of the β/α bands to λ = 532 and 559 nm in the UV–visible spectrum.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…This corresponds to the absorption spectra characteristic for P450s in the low-spin state, indicating the heme moiety of StaF to be present in its water-bound ferric form. Equivalent spectra were observed for related P450s such as StaH, OxyA tei , OxyB tei and OxyE tei , which are also involved in GPA cyclisation reactions [12,14,19,22]. Reduction of StaF by addition of sodium dithionite led to conversion of ferric to ferrous heme, which was accompanied by shift of the Soret maximum to λ = 422 nm and of the β/α bands to λ = 532 and 559 nm in the UV–visible spectrum.…”
Section: Resultsmentioning
confidence: 99%
“…Later diversification of the completely crosslinked peptide aglycones is the major source of diversity in natural GPAs, and occurs against the completed peptide aglycones [1,1011]. The installation of the crosslinks has received significant attention using both in vitro [1226] and in vivo [2732] techniques, largely due to the synthetic challenge that these modifications represent. In vivo studies initially confirmed that the cytochrome P450s, known as the Oxy enzymes, are each responsible for the installation of a single ring in the GPA aglycones and that there is a conserved order of activity in both type-I and type-IV GPAs.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…254 The X-domain is also required in the majority of cases to support efficient P450-catalysed crosslinking in vitro, with this requirement strictly enforced for OxyA and OxyE that act aer OxyB. 243,255,256,[258][259][260][261][262][263] Complestatin 264 and kistamicin 265 are structurally similar to GPAs, and also display several oxidative crosslinks whose generation has been ascribed to P450 enzymes, i.e. NRPS-bound modication with X-domain mediated P450 recruitment.…”
mentioning
confidence: 99%
“…We then tested the level of cyclisation seen in these peptides using the proven enzymatic coupling of OxyB van and OxyA tei , 7,[13][14][15]24,25 with the peptides themselves loaded onto a PCP-X di-domain construct excised from the final module of the teicoplanin NRPS machinery. 7 The results of the Oxy-catalysed turnover of peptides 4-5 demonstrated how vital the L-configuration of the C-terminal residue is for effective enzymatic crosslinking.…”
mentioning
confidence: 99%